الضغوط النفسية الناجمة عن الحجر الصحي في ظل جائحة كورونا (كوفيد-19) وأثرها على الصحة النفسية للمواطن الجزائري (دراسة ميدانية على مواطني دولة الجزائر) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: تهدف الدراسة إلى معرفة أثر الضغوط النفسية الناجمة عن الحجر الصحي في ظل جائحة كوفيد-19 على الصحة النفسية للمواطن الجزائري، بحيث تعد هذه الدراسة من الدراسات الوصفية التحليلية، استخدمت استبانة اشتملت داخلها على مقياسين هما مقياس الضغوط النفسية ومقياس الصحة النفسية بغرض جمع المعلومات وزعت إلكترونيا  على عينة قوامها 2504 مواطن ممن استجابوا لذلك، وبعد المعالجة الإحصائية للبيانات باستخدام 19 SPPS، خلصت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية بين الجنسين في الضغوط النفسية لصالح الذكور، كما وجدت فروق ذات دلالة إحصائية بين الجنسين عند متغير الصحة النفسية لصالح الذكور، بالإضافة إلى أن هناك علاقة ارتباطية عكسية بين كل من الضغوط النفسية والصحة النفسية وان المجتمع الجزائري يعاني من ضغوط نفسية مرتفعة ما أثر على انخفاض صحته النفسية خاصة عند الذكور لعدم تأقلمهم مع المكوث في البيت أثناء فترة الحجر الصحي.كلمات دالة: ضغوط نفسية، (كورونا) كوفيد-19، حجر صحي، صحة نفسية. Abstract:  The study aims to know the impact of psychological stress resulting from quarantine during of the Covid-19 pandemic on the mental health of the Algerian citizen, and this study is considered a descriptive and analytical study, used a questionnaire that included two scales (Psychological stress scale and Psychological Health Scale) was used for the purpose of collecting information, It was distributed electronically to a sample of )2504) Algerian citizens who responded to this. After statistical treatment of the data using 19 SPPS, the results of the study concluded that there are statistically significant differences Gender in psychological stress in favor of males, Also, statistically, significant differences were found between the sexes when the mental health variable in favor of males, In addition to that there is an inverse correlation between both psychological stress and mental health, and that the Algerian society suffers from high psychological pressures, which has affected their mental health negatively, especially for males because they were not able to adapt with staying at home during quarantine. Key words: Psychological stress; (Corona) Covid-19; Quarantine; Psychological Health.